Mešane Poissonove porazdelitve in njihova uporaba v kolektivnem modelu - Tavčar, Žan (Matrika, 2016)
Mixed distributions are basically distributions which parameter has its own distribution function. That idea gives us alternative model of data analysis. Its advantage is that we have more flexibility in our model, since parameter is also random variable. Conflict that lead us to use mixed distributions is that we are not sure what value does parameter take. We use mixed distributions to calculate distribution of number of claims. Typically, we use mixed Poisson distributions. They lead us to definition of negative binomial distributions, which is widely used in actuarial science, since it describes population which risk is not homogeneous.
Keywords: collective model; kolektivni model; matematika; mathematics; mešane Poissonove porazdelitve; mešane porazdelitve; mixed distributions; mixed Poisson distributions; probability; verjetnostni račun